Growth of Spinach Plant (Amaranthus tricolor L.) by Application of Kascing Organic Fertilizer and Bamboo Leaf Litter Mulch - Setiawati, Tia; Rahmawati, Fitryasari; Supriatun, Titin (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2018)
Spinach (Amaranthus tricolor L.). is one of the vegetables that are economically valuable with high nutrient content to support public health so that its production needs to be improved. The purpose of study was to obtained the optimal dosage of kascing organic fertilizer and the thickness of the bamboo leaf litter mulch on increase growth of spinach. The research used experimental method with randomize block design (RBD), two factors and three replications. The first factor was the adding of kascing organic fertilizer (K), consist of five levels doses, i.e: without adding kascing fertilizer (k0); 2.5 g/kg of soil (k1); 5 g/kg of soil (k2); 7.5 g/kg of soil (k3) and 10 g/kg of soil (k4). The second factor was bamboo leaf litter mulch (M), consist of three levels, i.e: without mulch (m0); mulch with thickness of 2.5 cm (m1); mulch with thickness of 5 cm (m2). Parameter observed were the plant height, the number of leaves, the leaf area, the shoot dry weight and the root dry weight. The data obtained was analyze using Anova and Duncan’s Multiple Range Test (α=5%). The results showed that interaction between dosage of kascing fertilizer with bamboos leaves litter mulch could increase the average of plant height (50.17 cm), number of leaves (40.33 leaves), shoot dry weight (5.77 g) and root dry weight (1.78 g) of spinach. Commonly, kascing organic fertilizer dose of 5 g/kg of soil (k2) and bamboos leaves litter mulch on the tickness of 5 cm (m2) combination was the best treatment for growth of spinach. Keywords: bamboo leaf litter, mulch, organic fertilizer of kascing, spinach